Implementation of Symptom Protocols for Nurses Providing Telephone‐Based Cancer Symptom Management: A Comparative Case Study. Issue 6 (31st May 2016) - Stacey, Dawn; Green, Esther; Ballantyne, Barbara; Tarasuk, Joy; Skrutkowski, Myriam; Carley, Meg; Chapman, Kim; Kuziemsky, Craig; Kolari, Erin; Sabo, Brenda; Saucier, Andréanne; Shaw, Tara; et al.
ABSTRACT: Background: The pan‐Canadian Oncology Symptom Triage and Remote Support (COSTaRS) team developed 13 evidence‐informed protocols for symptom management. Aim: To build an effective and sustainable approach for implementing the COSTaRS protocols for nurses providing telephone‐based symptom support to cancer patients. Methods: A comparative case study was guided by the Knowledge to Action Framework. Three cases were created for three Canadian oncology programs that have nurses providing telephone support. Teams of researchers and knowledge users: (a) assessed barriers and facilitators influencing protocol use, (b) adapted protocols for local use, (c) intervened to address barriers, (d) monitored use, and (e) assessed barriers and facilitators influencing sustained use. Analysis was within and across cases. Results: At baseline, >85% nurses rated protocols positively but barriers were identified (64‐80% needed training). Patients and families identified similar barriers and thought protocols would enhance consistency among nurses teaching self‐management. Twenty‐two COSTaRS workshops reached 85% to 97% of targeted nurses ( N = 119). Nurses felt more confident with symptom management and using the COSTaRS protocols ( p < .01). Protocol adaptations addressed barriers (e.g., health records approval, creating pocket versions, distributing with telephone messages). Chart audits revealed that protocols used were documented for 11% to 47% of patient calls. Sustained use requires organizational alignment and ongoing leadership support. Linking Evidence to Action: Protocol uptake was similar to trials that have evaluated tailored interventions to improve professional practice by overcoming identified barriers. Collaborating with knowledge users facilitated interpretation of findings, aided protocol adaptation, and supported implementation. Protocol implementation in nursing requires a tailored approach. A multifaceted intervention approach increased nurses' use of evidence‐informed protocols during telephone calls with patients about symptoms. Training and other interventions improved nurses' confidence with using COSTaRS protocols and their uptake was evident in some documented telephone calls. Protocols could be adapted for use by patients and nurses globally.